2021
DOI: 10.1093/jas/skab004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genomic predictions when new information is added

Abstract: The stability of genomic evaluations depends on the amount of data and population parameters. When the dataset is large enough to estimate the value of nearly all independent chromosome segments (~10K in American Angus cattle), the accuracy and persistency of breeding values will be high. The objective of this study was to investigate changes in estimated breeding values (EBV) and genomic EBV (GEBV) across monthly evaluations for 1 yr in a large genotyped population of beef cattle. The American Angus data used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Optimising expansion of the APY core subset with the arrival of new genotype data has not been addressed in the literature although several empirical studies have been done [36, 37, 38]. When new genotype data arrives, we can either construct the core subset anew or expand the existing core subset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimising expansion of the APY core subset with the arrival of new genotype data has not been addressed in the literature although several empirical studies have been done [36, 37, 38]. When new genotype data arrives, we can either construct the core subset anew or expand the existing core subset.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hidalgo et al . [38] examined the impact of adding new data with or without updating the core subset. They found that changes in GEBVs only slightly increased when the core was updated, compared to using the fixed core in the same period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors can also reduce the frequency of retraining. Hidalgo et al (2021) showed that the decay in predictive ability was less when the number of genotyped individuals with phenotypes was greater than the number of independent chromosome segments (ICS). The ICS was defined as four times the effective population size (Ne) and the length of the genome in Morgans (Stam, 1980), which can be approached by the number of largest eigenvalues explaining 98% of the variance in the genomic relationship matrix (Pocrnic et al,TABLE 2 | Rates of concordance between marker-based allele calls using flanking markers and the observed phenotype for five loci in the SoyNAM population.…”
Section: Discussionmentioning
confidence: 99%